The influence of the irrigant QMix on the push-out bond strength of a bioceramic endodontic sealer - Mustafa Gündoğar; Güzide Pelin Sezgin; Erhan Erkan; Özgün Yusuf Özyılmaz (Istanbul University, 2018)
Purpose The aim of this study was to evaluate the effect of a commercially available irrigant, the Qmix 2 in 1, on the push out bond strength of Endosequence BC which is a bioceramic based root canal sealer. Material and methods Sixty extracted maxillary central incisors were prepared with Protaper Next rotary instrument up to X4 (# 40). The specimens were randomly divided into four groups of equal sample size (n=15), according to the final irrigation regimen as follows: Group 1: 2.5% sodium hypochloride (NaOCl) (control), Group 2: 17% ethylenediaminetetraacetic acid (EDTA), Group 3: 2% Chlorhexidine (CHX), Group 4: QMix 2 in 1. After rinsing, teeth were obturated using gutta-percha with Endosequence BC sealer. Slices were obtained from coronal, middle, and an apical section of the root canal. Push-out test was performed to evaluate the bond strength between the root canal dentin and the sealer. Data was statistically analyzed. Results The push-out bond strength of the root canal sealer was significantly affected by the type of irrigation solution. Highest bond strengths were found in canals irrigated with Qmix solution, and these results were regardless of anatomical section of the root canal (p< 0.05). Conclusion Final irrigation of the root canals with QMix had a positive effect on the bond strength of Endosequence BC sealer throughout the root canal.